Enhancing Student Communication in Distance Learning through Zoom and Google Meet: Meningkatkan Komunikasi Siswa dalam Pembelajaran Jarak Jauh melalui Zoom dan Google Meet - Shobich , Achmad; Octavianto , Rozzy Aditya; Aldaffa , Moch. Akira Putra Adista Pratama; Abadi , Totok Wahyu (House of Wisdom: Journal on Library and Information Sciences, 2024)
This article conducts a bibliometric analysis of recent literature on the effectiveness of Zoom and Google Meet in enhancing student communication quality in higher education, particularly during the COVID-19 pandemic. Analyzing a dataset of 1000 papers from 2013 to 2023 sourced via Crossref, the study identifies trends, key themes, and prevalent research methodologies. Results indicate a significant rise in scholarly publications focusing on these virtual platforms. Visualizations highlight temporal publication patterns and densely researched areas. The findings underscore the growing importance of virtual platforms in education and provide insights for future research and educational practices. Highlights: Rising Scholarly Interest: Zoom and Google Meet in higher education publications. Temporal Analysis: Focus on 2020-2022 trends in research publications. Educational Insights: Guidance for effective distance learning strategies and research directions. Keywords: Zoom, Google Meet, distance learning, student communication, bibliometric analysis